The Role of Digital Marketing in Culinary Business Dynamics on Tiktok @Jihannnpp Account - Oktaviany, Fanny Intan; Senliana, Silma; Lestari, Aghnia Dian (Indonesian Journal of Advanced Research, 2024)
The Tiktok application is widely used by people to create and do business in Indonesia. The TikTok account @jihannnpp actively provides information about culinary places and food snacks in Cirebon. The purpose of this study is to find out the digital marketing techniques used by @jihannnpp Tiktok accounts. This study uses a qualitative method using data collection techniques. The data collection techniques used by the researcher are observation, interviews and documentation. The results of the research obtained through the Tiktok account @jihannnpp utilize digital marketing methods, namely digital marketing techniques, namely advertising techniques, hashtag techniques, promotion techniques, review techniques and distinctive characteristics. The results of advertising techniques to provide information, hashtag techniques to provide information, promotional techniques to introduce products and persuade followers and non-followers, review techniques to give reviews or assessments of the purchase consideration of a product, and characteristics on Tiktok accounts @jihannnpp to brand their character with the characteristic word "camatmam"